Association between single session service attendance and clinical characteristics in administrative data. (July 2021) - Edbrooke-Childs, Julian; Hayes, Daniel; Lane, Rebecca; Liverpool, Shaun; Jacob, Jenna; Deighton, Jessica
A large proportion of young people accessing specialist mental health services do so for a single session. The aim of the present study was to examine the characteristics of young people attending specialist mental health services for a single session and to examine associations between single session attendance and clinical characteristics. Secondary analysis of administrative data on N  = 23, 300 young people (mean age = 12.73 years, 57% female, 64% White British) was conducted. The mean number of sessions attended was 4.33 and 46% (10, 669) attended for a single session. Multilevel logistic regression analysis showed that younger children, Black young people (OR = 1.20, 95% CI = 1.01–1.43) or those whose ethnicity was not stated (OR = 1.25, 95% CI = 1.15–1.35), young people with peer relationship difficulties (OR = 1.11, 95% CI = 1.04–1.19) or low frequency problems (OR = 1.06, 95% CI = 0.99–1.14), and those with more complexity factors (OR = 1.07, 95% CI = 1.04–1.10) were more likely to attend services for a single session. The present study sets out research questions to prompt future research: (1) the experience of attending services for a single session, (2) identifying groups of single session attenders who do not require further support compared to those who are not able to sustain engagement with more sessions, and (3) whether new care pathways are needed for these groups who currently access specialist mental health services for a single session.